TIP OF THE TONGUE EXPERIENCE OMONG RADIO ANNOUNCER: A CASE STUDY ON AN FM RADIO STATION IN BANDUNG - Puspita Novianti Handayani, - (2008)
Abstract This research is entitled "Tip of the Tongue Experience among Radio Announcers". This study is aimed to uncover whether the distribution of tip of the tongue (TOT) among Radio announcers is phonologically, morphologically, or semantically motivated and to reveal what the respondents actually had in mind when they experienced tip of the tongue (TOT). This research uses a qualitative and descriptive method in approaching the phenomena. The respondents of this study are 10 announcers on FM Radio Station in Bandung, 7 males and 3 females; they are between 20-35 years. The required data were collected by using two research instruments: filling out the questionnaires and direct interview through tape recording. The collected data were then analyzed by using Brown and McNeill framework of tip of the tongue (TOT) in 1966. This research notifies that a Radio Station in Bandung experienced more tip of the tongue (TOT) in semantic patterns, that is, 50% or 21 from the total result of the distribution of tip of the tongue (TOT) along with the respondents is 42 and they experienced more spoken language in retrieval target words with the percentage 55.34% or 83 from the total result of the distribution of spoken and written language use along with the respondents is 150.